2022
DOI: 10.3390/bios12020114
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Vagus-Nerve Activity with Carbon Nanotube Sensors in Freely Moving Rodents

Abstract: The vagus nerve is the largest autonomic nerve and a major target of stimulation therapies for a wide variety of chronic diseases. However, chronic recording from the vagus nerve has been limited, leading to significant gaps in our understanding of vagus nerve function and therapeutic mechanisms. In this study, we use a carbon nanotube yarn (CNTY) biosensor to chronically record from the vagus nerves of freely moving rats for over 40 continuous hours. Vagal activity was analyzed using a variety of techniques, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…The ability to record neural signals selectively over an extended period has been difficult due to the degradation of electrode performance and encapsulation at the implantation site, hindering the widespread use of this technology in human patients for sensory and motor restoration. Previous research has shown that CNTY electrodes can be used for long-term interfacing with the rat vagus nerve to record vagal tone and decode vagus nerve activity for various behaviors [20,22]. The size of individual fascicles in the rat sciatic nerve ranges from 15-300 µm in diameter [30], similar to the size of the rat vagus nerve, which ranges from ∼250-500 µm in diameter [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to record neural signals selectively over an extended period has been difficult due to the degradation of electrode performance and encapsulation at the implantation site, hindering the widespread use of this technology in human patients for sensory and motor restoration. Previous research has shown that CNTY electrodes can be used for long-term interfacing with the rat vagus nerve to record vagal tone and decode vagus nerve activity for various behaviors [20,22]. The size of individual fascicles in the rat sciatic nerve ranges from 15-300 µm in diameter [30], similar to the size of the rat vagus nerve, which ranges from ∼250-500 µm in diameter [20].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated that flexible electrodes like carbon nanotube yarn (CNTY), which possess a flexural rigidity similar to small nerves, can produce reliable and stable chronic recordings in the autonomic nervous system [20][21][22]. Based on this, we hypothesize that CNTY electrodes can also offer high SNR for recording neural activity in the peripheral somatic nervous system over extended periods.…”
Section: Introductionmentioning
confidence: 94%
“…On the computational side, since the drift in the amplitudes of signals and changes in the signal-to-noise ratio greatly hampers chronic neural recordings and decoding, new algorithms for drift compensation have been developed ( 173 ). In the case of the VN, carbon nanotube yarn electrodes have been used to make the first direct chronic measurements of vagal tone in freely moving rats ( 174 ). Thanks to their small size, high flexibility, and low impedance, carbon nanotube yarn electrodes have provided stable, high-signal-to-noise chronic recordings in rats VN with high-quality signals continuing up to 4 months after implantation ( 174 ).…”
Section: Vagus Nerve Stimulation For Cardiovascular Diseasesmentioning
confidence: 99%
“…In the case of the VN, carbon nanotube yarn electrodes have been used to make the first direct chronic measurements of vagal tone in freely moving rats ( 174 ). Thanks to their small size, high flexibility, and low impedance, carbon nanotube yarn electrodes have provided stable, high-signal-to-noise chronic recordings in rats VN with high-quality signals continuing up to 4 months after implantation ( 174 ).…”
Section: Vagus Nerve Stimulation For Cardiovascular Diseasesmentioning
confidence: 99%
“…In [ 10 ], the authors use a carbon nanotube yarn (CNTY) biosensor to chronically record from the vagus nerves of freely moving rats for over 40 continuous hours. Vagal activity is analyzed and spike-cluster-firing rates are found to correlate with food intake.…”
Section: Introductionmentioning
confidence: 99%